Quality in early childhood services : an international perspective - Penn, Helen (Open University Press, 2011)
Examines how quality and good practice in early childhood education and care (ECEC) is interpreted and implemented in a variety of settings and circumstances. This book considers the variety of rationales that inform services for early childhood education and care